2003
DOI: 10.1093/oxfordjournals.rpd.a006162
|View full text |Cite
|
Sign up to set email alerts
|

A survey of 14 computed tomography scanners in Greece and 32 scanners in Italy: Examination frequencies, dose reference values, effective dose and doses to organs

Abstract: A survey of examination frequencies, dose reference values, effective doses and doses to organs involving 14 scanners from Greece and 32 scanners from Italy was carried out for the years 1999 and 2000. Examination frequencies per scanner and per year were found to be 3590 for Greece and 4520 for Italy. For the types of examinations considered, CDTI(W) and DLP measurements were taken. Also scan lengths used for the same types of examinations were monitored. For the same types of examinations effective doses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
2
11
2
1
Order By: Relevance
“…On the other hand, the mean DLP for abdominal CT (495.5 mGy.cm) is similar to the values reported by Papadimitriou et al (493 mGy.cm -551 mGy.cm) [8] . But in this study their values were based on CT scan of upper abdomen only and thus the region scanned was small.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the mean DLP for abdominal CT (495.5 mGy.cm) is similar to the values reported by Papadimitriou et al (493 mGy.cm -551 mGy.cm) [8] . But in this study their values were based on CT scan of upper abdomen only and thus the region scanned was small.…”
Section: Discussionsupporting
confidence: 90%
“…The average CTDI value (7.42 mGy) in our study was lower than that reported by IAEA 16.2 mGy [7] and that by Papadimitriou et al (21 mGy) [8] . Torp et al [9] reported results from five countries in the Nordic region in which the weighted CTDI values ranged from 10.5 to 11.7 mGy.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Where comparison is possible, the results of this and previous reports are summarised in Table 7. Only Papadimitriou et al [24] investigated all seven protocols covered here, although in a smaller number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is not appropriate to set dose limits on medical exposures, DRL is a useful quantity that facilitates the investigation of dose levels in various CT procedures and permits comparison of performance between different scanners and techniques [22]. DRLs provide the means to improve patient protection, if it is required, identify poor performance and monitor CT performance in periodic measurements [24-27]. The foregoing discussion reveals the need for proper management of radiation dose in a CT facility.…”
Section: Introductionmentioning
confidence: 99%